PENERAPAN PERMAINAN MISTERY BAG SEBAGAI STRATEGI PEMBELAJARAN KOSAKATA BENDA BAHASA JEPANG PADA SISWA KELAS XI TAHUN AJARAN 2014 SMK KANSAI PEKANBARU - Kharlina, Debby Afriyanti; Basri, Merri Silvia; Budiani, Dini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study sought to determine the results of the questionnaire and interview students regarding the application of the game Mystery Bag in learning Japanese. This study also aims to determine students' responses about the game Mystery Bag that is, a positive thing that obtained by the students, and the constraints faced by the students to the application of the game Mystery Bag in learning Japanese. The response is in the form of fun or learn Japanese after the implementation of the game Mystery Bag in learning Japanese. The population in this study is a class XI student of SMK Accounting Kansai Pekanbaru many as 25 people. Qualitative descriptive methods used in this study so that in this study only explain, describe, and explain the data obtained. From the analysis of the data can be obtained in the form of positive things: 1) based on results of a questionnaire, 92% of respondents replied that students feel to learn Japanese to be more enjoyable after the implementation of the game Mystery Bag in learning Japanese, 80% of students felt helped by the implementation of the game Mystery Bag can make it easier to memorize vocabulary and increase vocabulary has not been studied, 88% of students can be motivated to learn Japanese with the game Mystery Bag, 100% of students preferred learning Japanese with the game Mystery Bag, and 84% of students agree when the game Mystery Bag applied in learning Japanese. 2) the constraints faced by students when the application of the game Mystery Bag is the pronunciation of the difficult vocabulary, the lack of cohesion in the team and the implementation time of less research time. This study can be used as a learning strategy in Japanese. Based on research results that have been obtained, it is expected to further research to better take into account the timing of the game well.Keywords: vocabulary, positives constraints, game mystery bag